The Importance of Inflammation Markers in Heart Failure Patients With Appropriate Or Inappropriate ICD Shock - Seyis, Sabri; Kurmus, Ozge (Cardiology and Cardiovascular Medicine, 2017)
Background: C-reactive protein (CRP), neutrophil lymphocyte ratio (NLR), and platelet lymphocyte ratio (PLR) are associated with the prognosis of cardiovascular diseases such as coronary artery disease, acute myocardial infarction, and heart failure. However, their prognostic significance is unknown in the heart failure patients with implantable cardioverter defibrillator (ICD) devices. Objective: The aim of this study is to evaluate the levels of inflammation markers (CRP, NLR, and PLR) in patients with ICD who have received no shock during 3 years of follow-up and in those who have received appropriate or inappropriate shock, and to determine importance of inflammatory markers in ICD patients who received shock delivery. Results: There was a statistically significant difference between the groups in terms of gender and age (p=0.013, p<0.001, respectively). Patients who have received appropriate or inappropriate shock were older and mostly male. There was no statistically significant difference between groups in terms of mean NLR and PLR values (p>0.05). In ICD patients who have received appropriate or inappropriate shock, the highest AUC value was found for CRP in the receiver operating characteristic curve assessment. Conclusion: Our results show that the NLR, PLR, WBC values cannot be used to determine ICD shock while it suggests CRP may be.